Frekwencja a przemiany współczesnej normy wymawianiowej (w świetle dyskusji na temat NRSF Witolda Mańczaka) - Halina Kurek (Ksiegarnia Akademicka Publishing, 2016)
Frequency and changes in the contemporary orthophonic standard (in light of the discussion about Witold Mańczak’s irregular phonetic development caused by frequency)